2010
DOI: 10.1155/2010/184152
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Family Carers of Community-Dwelling Elder with Cognitive Decline: A Randomized Controlled Trial

Abstract: Objective. Caring for a patient with cognitive decline has an important impact on the general well-being of family caregivers. Although highly appreciated, interventions in dementia home care remain mainly ineffective in terms of well-being. Consequently, in spite of an extensive support system, abrupt ending of home care remains more rule than exception. Method. The hypothesis was that the intervention of a care counselor, coordinating care in quasi-unstructured way during one year, will alleviate caregivers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 47 publications
(49 reference statements)
0
49
0
Order By: Relevance
“…This syndrome is similar to what was found in this group of IC in which the most outstanding or above problems are related to sleep difficulties, fatigue, corroborated as mental health problems; other studies also report problems as depression, [22] anxiety [23] and anger. [24] However, many ICs show emotional problems without being necessarily ratified by clinical diagnostic criteria for the mood or anxiety disorder. So it is common the presence of symptoms such as difficulty to fall asleep, as evidenced in the present study, feelings/emotions of hopelessness, worry about the future, among others.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is similar to what was found in this group of IC in which the most outstanding or above problems are related to sleep difficulties, fatigue, corroborated as mental health problems; other studies also report problems as depression, [22] anxiety [23] and anger. [24] However, many ICs show emotional problems without being necessarily ratified by clinical diagnostic criteria for the mood or anxiety disorder. So it is common the presence of symptoms such as difficulty to fall asleep, as evidenced in the present study, feelings/emotions of hopelessness, worry about the future, among others.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The effects on the needs for early diagnosis, financial and legal aspects of the disease, and meaningful activities were not studied. CM was not found to have any effect on patients' daily activities, cognition and depression.A meta-analysis of the effects of CM (Figure 1 and Supplemental Appendix 4, available at http:// 61,62,66,73,74,76,81,85,91,93,95,97 Canada 84 USA [14][15][16] Europe (21 studies) UK 20,52,53,64,69,72,77,78,83,84,99 The Netherlands The effect on depression of caregivers was uncertain (SMD -0.23, 95% CI, -0.46 to 0.01, P = .06), 14,17,18 and there was no effect on caregivers' burden (SMD 0.17, 95% CI, -0.18 to 0.52, P = .34). …”
mentioning
confidence: 99%
“…15,16,20 Moreover, as the first point of contact for the dyad, they appear to be more easily reachable than family physicians. [14][15][16][17][18][20][21][22] Our previous studies demonstrated that the effectiveness of CM depends on a small caseload, regular and proactive follow-up, and transparent communication among health care professionals. …”
mentioning
confidence: 99%
See 2 more Smart Citations